EDUKASI PROGRAM PENGEMBANGAN KEWIRAUSAHAAN PEMUDA - Budiningtyas, Dwi Putri (Yayasan Cita Cendikiawan Al Kharizmi, 2024)
The purpose of this service is a youth organization, for example the Karang Taruna organization, which is empowering village communities in the fields of economy, social, sports and production to improve social welfare. This social organization is a forum/media for developing the younger generation who grow and develop on the basis of social awareness and responsibility from, by and for the community in the village area. The implementation method for this community service program is by means of lectures, questions and answers and socialization. The results achieved in this empowerment activity are increasing interest and participation of residents, especially Karang Taruna in positive activities and having income. In conclusion, a productive business that can be done in the near future is a pond fishery business, because there are several ponds that have not been filled with fish.